Orthodontic and Orthognathic Surgical Treatment of a Pediatric OSA Patient - Gregory W. Jackson (Case Reports in Dentistry)
A case report is presented which demonstrates the effectiveness of comprehensive orthodontic treatment combined with orthognathic surgery in the correction of malocclusion and reduction in the sequelae of Obstructive Sleep Apnea (OSA). The patient’s severe OSA was improved to very mild as evaluated by full overnight polysomnogram. The orthodontic treatment included the expansion of both dental arches and mandibular advancement surgery. There was significant improvement in the patient’s sleep continuity and architecture with the elimination of obstructive apneas.